Fraunhofer LBF develops lignin-based flame retardant from paper manufacturing waste. Issue 12 (December 2017) - Unknown
Abstract : Germany's Fraunhofer Institute for Structural Durability and System Reliability (Fraunhofer LBF) reports that it has developed technology to chemically bond phosphorus to the lignin residue from papermaking, and has demonstrated that the resulting phosphorylated product can be used as a flame retardant for polymers.